Selective autophagic degradation of ACLY (ATP citrate lyase) maintains citrate homeostasis and promotes oocyte maturation. Issue 1 (2nd January 2023) - He, Hainan; Wang, Junling; Mou, Xingmei; Liu, Xin; Li, Qiao; Zhong, Mingyue; Luo, Bingbing; Yu, Zhisheng; Zhang, Jingjing; Xu, Tian; Dou, Chengli; Wu, Danya; et al.
ABSTRACT: Macroautophagy/autophagy is a cellular and energy homeostatic mechanism that contributes to maintain the number of primordial follicles, germ cell survival, and anti-ovarian aging. However, it remains unknown whether autophagy in granulosa cells affects oocyte maturation. Here, we show a clear tendency of reduced autophagy level in human granulosa cells from women of advanced maternal age, implying a potential negative correlation between autophagy levels and oocyte quality. We therefore established a co-culture system and show that either pharmacological inhibition or genetic ablation of autophagy in granulosa cells negatively affect oocyte quality and fertilization ability. Moreover, our metabolomics analysis indicates that the adverse impact of autophagy impairment on oocyte quality is mediated by downregulated citrate levels, while exogenous supplementation of citrate can significantly restore the oocyte maturation. Mechanistically, we found that ACLY (ATP citrate lyase), which is a crucial enzyme catalyzing the cleavage of citrate, was preferentially associated with K63-linked ubiquitin chains and recognized by the autophagy receptor protein SQSTM1/p62 for selective autophagic degradation. In human follicles, the autophagy level in granulosa cells was downregulated with maternal aging, accompanied by decreased citrate in the follicular fluid, implying a potential correlation between citrate metabolism and oocyte quality. We also show that elevated citrate levels in porcine follicular fluid promote oocyte maturation. Collectively, our data reveal that autophagy in granulosa cells is a beneficial mechanism to maintain a certain degree of citrate by selectively targeting ACLY during oocyte maturation. Abbreviations: 3-MA: 3-methyladenine; ACLY: ATP citrate lyase; AMA: advanced maternal age; CG: cortical granule; CHX: cycloheximide; CQ: chloroquine; CS: citrate synthase; COCs: cumulus-oocyte-complexes; GCM: granulosa cell monolayer; GV: germinal vesicle; MII: metaphase II stage of meiosis; PB1: first polar body; ROS: reactive oxygen species; shRNA: small hairpin RNA; SQSTM1/p62: sequestosome 1; TCA: tricarboxylic acid; TOMM20/TOM20: translocase of outer mitochondrial membrane 20; UBA: ubiquitin-associated domain; Ub: ubiquitin; WT: wild-type